Effectiveness of the Ten-valent Pneumococcal Conjugate Vaccine Against Tympanostomy Tube Placements in a Cluster-randomized Trial. Issue 11 (November 2015) - Palmu, Arto A.; Jokinen, Jukka; Nieminen, Heta; Rinta-Kokko, Hanna; Ruokokoski, Esa; Puumalainen, Taneli; Traskine, Magali; Moreira, Marta; Borys, Dorota; Schuerman, Lode; Kilpi, Terhi M.
Abstract : Background: We evaluated the impact of the new pneumococcal Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10, GSK Vaccines) on tympanostomy tube placements (TTPs). Methods: Finnish Invasive Pneumococcal disease vaccine trial was a nationwide phase III/IV cluster-randomized, double-blind trial. Children younger than 19 months received PHiD-CV10 in two thirds of clusters (N = 52) or hepatitis B or A vaccine as control in 26 clusters according to 3 + 1 or 2 + 1 schedules (infants younger than 7 months) or catch-up schedules. A secondary objective of the trial was to assess vaccine effectiveness (VE) against TTPs in children who received at least one vaccine dose before or after 7 months of age. Blinded follow-up lasted from the date of first vaccination (from February 2009 through October 2010) to December 31, 2011. Outcome data were collected through the National Care register and Social Insurance Institution reimbursement register. Results: More than 47, 000 children were enrolled. In 30, 527 infants younger than 7 months of age at enrolment, 4369 TTPs were reported in 3594 subjects. The incidence was 7.9 per 100 person-years in the infant control cohort. The VE estimate was 13% [95% confidence interval (CI): −2% to 26%] for combined PHiD-CV10 3 + 1 and 2 + 1 infant schedules. The VE estimates for the 3 + 1 and 2 + 1 infant schedules when estimated separately were similar. For the catch-up schedules, the VE was 11% (95% CI: −7% to 26%) for children enrolled at 7–11 months of age and −1% (95% CI: −21% to 16%) for children enrolled at 12–18 months of age. Conclusions: Our study results suggest that PHiD-CV10 immunization according to a 3 + 1 or 2 + 1 schedule initiated before 12 months of age may reduce the frequency of TTPs, although the primary analysis did not reach statistical significance. Abstract : Supplemental Digital Content is available in the text.